Early nurse-initiated enteral nutrition and its impact on postoperative recovery and complication rates: a meta-analysis of surgical patient outcomes - Shi, Biao; Shen, Lan; Xu, Zhengying; Yu, Binhua; Yang, Xiao; Yang, Hongcui; Chen, Chaoming (Frontiers in Nutrition, 2025)
BackgroundNutritional support after surgery is an essential part of recovery augmentation protocols, especially in high-risk surgical patients. Early enteral nutrition (EEN) within 24–48 h after surgery has been argued to enhance gastrointestinal function, decrease complications, and minimize hospital stay. The purpose of this research was to provide clinical study evidence synthesis on the effect of EEN on postoperative recovery and complication rates for varying surgical patient populations.Methodology30 clinical trials, with 1996–2023 information, of 2,432 patients undergoing surgery, equally divided into early enteral/oral nutrition (EEN) and standard enteral/oral nutrition (SEN) groups, were compared. The randomized controlled trials (RCTs), prospective and retrospective cohort designs, as well as observational analysis studies, comprised the studies. Populations included neonates, pediatric cardiovascular patients, adults with gastrointestinal, oncologic, and emergency abdominal surgery. Sample size, type of intervention, duration, outcomes, and complications were extracted data.ResultsEEN was linked with shorter hospital stay, earlier return of bowel function, better weight gain, increased immune and nutritional status, and reduced rates of postoperative complications, especially infections. Adverse events like anastomotic leaks or feeding intolerance were not significantly increased. Most RCTs proved to have significant advantages in early initiation of feeding over traditional delayed protocols.ConclusionEarly enteral nutrition is a safe and effective method for optimizing postoperative recovery in a wide range of surgical patients. It profoundly improves clinical results without raising the risk of complications. These results justify the incorporation of EEN into routine postoperative care pathways.